Quelques Diptères Dolichopodides (Deuxième article). - Parent, Octave (Contributions to Entomology = Beiträge zur Entomologie, 1954)
Nomenclatural Acts flavizonatus Parent, 1954 (Condylostylus), spec. n. vaalensis Parent, 1954 (Hydrophorus), spec. n. bicolor Parent, 1954 (Nematoproctus), spec. n. apicalis Parent, 1954 (Paraclius), spec. n. bidilatata Parent, 1954 (Porphyrops), spec. n. peregrinus Parent, 1954 (Syntormon), spec. n. anale Parent, 1954 (Syntormoneurum), spec. n.